2001
DOI: 10.1590/s0004-282x2001000100008
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in children with cerebral palsy

Abstract: Objective: To describe the prevalence and characteristics of epilepsy in patients with cerebral palsy in a tertiary center. Methods: a total of 100 consecutive patients with cerebral palsy were retrospectively studied. Criteria for inclusion were follow-up period for at least 2 years. Types and incidence of epilepsy were correlated with the different forms of cerebral palsy. Other factors associated with epilepsy such as age of first seizure, neonatal seizures and family history of epilepsy were also analysed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
49
1
9

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 18 publications
11
49
1
9
Order By: Relevance
“…24 In this study, history of epilepsy in the family was not proven to be a risk factor for epilepsy in spastic CP children. Kulak et al and bruck et al 15 showed different result that may due to information bias about the history of epilepsy in the family in this study. This could happen because of the low education level of parents which causes limited knowledge of epilepsy.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…24 In this study, history of epilepsy in the family was not proven to be a risk factor for epilepsy in spastic CP children. Kulak et al and bruck et al 15 showed different result that may due to information bias about the history of epilepsy in the family in this study. This could happen because of the low education level of parents which causes limited knowledge of epilepsy.…”
Section: Discussioncontrasting
confidence: 56%
“…In this study, epilepsy was found in 50% and 38% subjects with spastic hemiplegia and spastic quadriplegia CP, respectively. bruck et al 15 found a higher prevalence of epilepsy in spastic CP children (62%). This might be due to the higher number of epilepsy found in the spastic hemiplegia (70.6%) and spastic quadriplegia (66.1%) patients compared to this study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Carlsson et al reported epilepsy in 38% of 146 Swedish children with cerebral palsy, and found that epilepsy was more common in children with cognitive disability [7]. Bruck et al looked at 100 children with cerebral palsy with at least 2 years of follow-up data, and found an overall epilepsy rate of 62%, with a rate of 71% in children with hemiplegic cerebral palsy [8]. Zafeiriou et al found an overall epilepsy rate of 36% in 178 consecutive patients with cerebral palsy, with a rate of 42% in patients with hemiplegic cerebral palsy [9].…”
Section: Discussionmentioning
confidence: 99%
“…In 54 children (62%), a physician diagnosis of cerebral palsy was recorded in the medical record. Children who presented with stroke during the neonatal period were more likely to have multiple infarcts (29% vs 3%, p 5 0.001), were younger when they began walking (median age of 13 [IQR 10-17] vs 16 [IQR [13][14][15][16][17][18][19][20][21][22] months, p 5 0.04), and were less likely to have a cerebral palsy diagnosis recorded (50% vs 85%, p 5 0.001) (table e-2). Otherwise, demographics, birth history, and years of follow-up were similar between the 2 groups.…”
mentioning
confidence: 99%